The Concept of Allah’s Help in the Qur'an Towards the Sociology of Life - Aisya Rahma El-Fani; Cecep Sobar Rochmat; Nurul Salis Alamin; Najma Ulayya AlFany (al-Afkar, Journal For Islamic Studies, 2024)
In human life there are many problems that will be faced so that all problems will not be resolved without help from Allah. Throughout human history, religion and belief have played an important role in shaping the values, behavior and social structure of society. One important aspect of religious belief is the concept of Allah or God's help, which has a significant impact on the outlook on life of individuals and society. This research has important relevance in further understanding how religion influences society and social dynamics. This research is qualitative research in which all data collection is taken using library research by analyzing books or articles related to the research subject. Meanwhile, the approach used is a qualitative analytical descriptive approach by describing and describing data from primary and secondary readings and then analyzing them to draw conclusions.